On Different Approaches for Integrals of Physical Dynamical Systems - Virdi, Jasvinder Singh (Discontinuity, Nonlinearity, and Complexity, 2026)
For driven time dependent harmonic oscillator a detailed and systematic study of several methods for the building of Integrals is carried out. The central feature of the present discussion is the establishment of Integrals for the dynamical system. In spite of their different procedural details all the approaches lead to the same invariant for the given classical system. Advantage and limitations of different methods are briefly highlighted.